CARACTERISATION OPTIQUE ET ELECTRONIQUE DES SEMICONDUCTEURS AMORPHES PAR LA TECHNIQUE DE PHOTOCOURANT CONSTANTOptical and electronic characterization of amorphous semiconductors by means of constant photocurrent method in the continuous regime (DC-CPM) - TIBERMACINE, T.; MERAZGA, A. (Courrier du Savoir; Vol. 10 (2010): Courrier du Savoir)
We present in this article the optical and electronic properties of amorphous semiconductors in particular hydrogenated amorphous silicon a-Si: H. Two samples, undoped and P-doped, are prepared by plasma enhanced chemical vapour deposition (PECVD). The optical absorption coefficient of the two samples is measured by the constant photocurrent technique in continuous mode (DC-CPM). Then the measured absorption spectra are converted into electronic density of states (DOS) within the mobility gap. We have also developed a computer program to model DC-CPM by holding into account all the possible thermal and optical transitions between the localized states in the gap and the extended states in the conduction and valence band. The defect pool model for the electronic density of states (DOS) is incorporated in our modelling. Our measurements show that the DC optical coefficient absorption is underestimated only for the undoped sample. Our modelling showed us the importance to consider the two absorption coefficients due to the electrons and to the holes to reconstruct the density of the occupied and non-occupied states within the gap mobility of the material.